Diagnostic Accuracy of Drop Hydrogen Peroxide Test as a Novel Bedside Diagnostic Test to Differentiate Transudative and Exudative Pleural Effusion Against Light’s Criteria - Vaidya, N.; Sapkota, P.; Chaurasia, S.; Thapa, B.; Bhandari, N.; Bhattarai, I. (Kathmandu University Medical Journal, 2022)
Background Diagnostic evaluation of pleural fluid according to Light’s criteria to differentiate between exudative and transudative fluid takes 1 or 2 working days. For rapid clinical management, especially in critically ill patients, a simpler bedside diagnostic test can be done which has similar diagnostic accuracy as that of Light’s Criteria. Objective To determine the diagnostic accuracy of Drop Hydrogen Peroxide test to differentiate exudative and transudative pleural effusion in comparison to Light’s criteria. Method A concurrent validity test was performed using a convenient sampling technique including patients presenting to the Department of Internal Medicine from January to September 2021, who had pleural effusion. Two milliliters of tapped pleural fluid of patients who underwent aseptic thoracocentesis was collected in a test tube to which one to two drops of 20% hydrogen peroxide was added. Presence of bubbles suggested an exudative type of fluid. Rest of the tapped pleural fluid was sent to the laboratory for further evaluation by Light’s criteria, which was compared with the results by Drop Hydrogen Peroxide Test. Result There were 83 patients who had pleural effusion, of them a total of 43 patients had transudative pleural effusion while 40 patients had exudative pleural effusion based on Light’s criteria and 37 patients had transudative pleural effusion while 46 patients had exudative pleural effusion based on drop hydrogen peroxide test. Conclusion The drop hydrogen peroxide test allows cost effective and prompt evaluation of the type of pleural effusion is exudative or transudative, thereby making it a convenient diagnostic bedside test.